Exile as an Institutional Response to Authoritarian Interference - O’Connell, Carly; Long, Kyle (International Higher Education, 2024)
This article introduces the concept of “university in exile” and situates this phenomenon in the context of rising authoritarianism around the world. The authors examine the causes and consequences of HEIs going into exile by considering five examples. They conclude that democratically-oriented HEIs with strong global partnerships are the most likely both to go into exile and to survive it, and argue that defenders of democracy around the world should support these institutions.